1995
DOI: 10.1080/09553009514550371
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Micronucleus and Apoptosis Assays with Reproductive Cell Death

Abstract: The relationship between ionizing radiation-induced cell killing and DNA damage measured by the micronucleus and apoptosis assays was determined in three established cell lines (L929, HL-60, and Chang). Irradiation experiments revealed a dose-dependent increase of micronucleated cells until a certain dose was reached. Above this dose no further increase of the micronucleus frequency was observed, but in HL-60 and Chang cells additional DNA fragmentation was detected by morphological criteria, characteristic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 32 publications
6
14
0
2
Order By: Relevance
“…These data suggest that the increased cell death by the combined treatment could be accounted for by the sum of the micronucleated and apoptotic cells in the irradiated population. This observation is in agreement with Abend et al (39), who found that for three cell lines, including HL-60, the summation of two kinds of cellular damage, micronuclei production and apoptosis, correlated well with cell clonogenic survival.…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that the increased cell death by the combined treatment could be accounted for by the sum of the micronucleated and apoptotic cells in the irradiated population. This observation is in agreement with Abend et al (39), who found that for three cell lines, including HL-60, the summation of two kinds of cellular damage, micronuclei production and apoptosis, correlated well with cell clonogenic survival.…”
Section: Discussionsupporting
confidence: 82%
“…p53 requirement Although HL60 cells are generally considered null for p53 (Wolf and Rotter, 1985), at least one subclone of these cells has been reported to contain p53 (Hopcia et al, 1996). Di erences in the endogenous p53 status may contribute to substantial di erences in the intrinsic radiosensitivity of several available subclones of the HL60 cells (Abend et al, 1995;Hopcia et al, 1996;Makepeace et al, 1996). We conĀ®rmed the lack of endogenous p53 in the clone used in the present study ( Figure 6).…”
Section: Characterization Of Csa-19supporting
confidence: 59%
“…Typical normal urothelial cells are shown in ( Figure 1C). Samples were scored for the presence of micronucleated ( Figure 1D) and apoptotic ( Figure 1E, F) cells measured as total cell damage (Abend et al, 1995(Abend et al, , 2000. Micronuclei appeared as green-coloured round bodies separated from the main nucleus as previously described (Belyakov et al, 1999).…”
Section: Scoring Of Micronucleated and Apoptotic Cellsmentioning
confidence: 99%